El problema de los indiscernibles en el arte y el contexto artístico como solución - Arroyo Bejarano, Kevin (2025)
The following paper aims to present “the artistic context” as the central element in resolving the problem of indiscernibles in art. It is known that one of the greatest challenges currently existing in the philosophy of art is both the nature and identification of contemporary plastic artworks. This is mainly due to the use of common objects as artistic material. Faced with the problem, the article suggests that “the artistic context” is what primarily can support and explain the identification and assignment of the “art” category to certain objects. To achieve this goal, the problem will be presented through Arthur Danto and the reponses of the neowittgensteinians regarding the “family resemblance” and Nelson Goodman with his symbolic theory of art will be criticized. Then, the response of the artistic context will be provided as the most suitable.